1991
DOI: 10.2307/3350121
|View full text |Cite
|
Sign up to set email alerts
|

The Autopsy Crisis Reexamined: The Case for a National Autopsy Policy

Abstract: The use of autopsy in medical practice in the United States has declined drastically over the past 25 years. Physicians conduct post-mortem examinations on less than 12 percent of persons who die in hospitals and on proportionally far fewer people who die at home. Without due assessment of causes of death, pathologists lose opportunities to conduct critical diagnostic exercises, and society fails to obtain accurate health statistics. Medical practitioners, legislators, insurers, and the public should consider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…While autopsies conceptually contribute to auditing of aspects of medical care, to the best of our knowledge, no studies have shown that conducting autopsies and publicizing the findings are directly beneficial for patients [ 22 ]. No data have substantiated the notion that autopsy practice improves quality of patient care.…”
Section: Autopsies As Quality Management Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…While autopsies conceptually contribute to auditing of aspects of medical care, to the best of our knowledge, no studies have shown that conducting autopsies and publicizing the findings are directly beneficial for patients [ 22 ]. No data have substantiated the notion that autopsy practice improves quality of patient care.…”
Section: Autopsies As Quality Management Toolmentioning
confidence: 99%
“…In spite of this lack of an evidence base, many clinicians and pathologists have experienced the teaching effect of an unexpected autopsy diagnosis, which may be beneficial for many patients to come, however difficult this might be to measure. Most commonly, autopsy reports reside in the obscurity of pathology and medical records departments as orphan data, because they are not systematically evaluated [ 22 ].…”
Section: Autopsies As Quality Management Toolmentioning
confidence: 99%
“…There are no data to support the widespread belief that autopsies lead to improvements in patient care (33). This could mean that belief in the qualitative importance of autopsies really is a "matter of faith," and that doubters can cite a lack of evidence.…”
Section: Measuring the Quality Effects Of Autopsymentioning
confidence: 98%
“…The legal regulation of post-mortem clinical training practice is thus often included in autopsy legislations [71] Quality control of public statistics Being considered "gold standard" for cause of death, autopsy results are used for correction of public statistics [72]. Low autopsy rates worldwide endanger adequate distribution of funding of various diseases [73,74] Tissue sampling and research Autopsies remain a major source for sampling of fluids, cells, and tissues. As a substitute for the full, conventional post-mortem, f.e.…”
Section: Training In Medical Proceduresmentioning
confidence: 99%